(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
The Cadmium (Cd) and lead (Pb) are toxic heavy metals able to cause diseases in humans. The aim of this study was to detect the presence of Cd and Pb in ultra-pasteurized, pasteurized and powdered cow milk marketed in the city of Guayaquil. For this purpose, different presentations and brands of milk were sampled: pasteurized (three brands), ultra-pasteurized (eight brands) and powdered milk (five brands). The samples were digested with nitric acid: hydrogen peroxide and the heavy metal concentration was detected using an Atomic Absorption Spectrophotometer (Perkin-Elmer). Heavy metals were not detected in liquid and ultra-pasteurized milk the. However, in powdered milk, high concentrations of Pb (5.450 ± 2.474 ppm) and Cd (0.333 ± 0.176 ppm) were detected. The Pb values are 272 times higher than the permitted maximum level for milk according to Codex Alimentarius (0.02 ppm). As a permitted maximum level of Cd for milk does not exist, the generation of a maximum allowed value is proposed in Ecuador.